2021
DOI: 10.1108/mrr-07-2021-0514
|View full text |Cite
|
Sign up to set email alerts
|

The effect of workplace bullying on burnout: the mediating role of affective well-being

Abstract: Purpose This study aims to examine the impact of workplace bullying on employees’ burnout by investigating the mediating effect of affective well-being (AWB). Design/methodology/approach Data of 532 employees from diverse organizations in Portugal were collected. These data were collected using anonymously completed structured questionnaires available online. Findings The results support the research hypotheses proposed, confirming that workplace bullying is related to both AWB and burnout. Moreover, affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 88 publications
(155 reference statements)
0
4
0
Order By: Relevance
“…The experience of a stressful teaching work environment also has clinical implications for burnout syndrome. Burnout has been defined as "a psychological syndrome emerging as a prolonged response to chronic interpersonal stressors on the job" [40] (p. 103) and, therefore, as an occupational psychological syndrome [41][42][43], often affecting medical professionals, teachers, police officers, army soldiers, and many other professionals [44][45][46][47][48][49][50][51][52][53]. Certain studies have detected relationships between burnout and EI [54,55], as an important personal resource that can facilitate effective emotion regulation [56] and play a crucial role in teachers' occupational well-being models [57].…”
Section: The Role Of Emotional Intelligence and Metacognition In Rela...mentioning
confidence: 99%
“…The experience of a stressful teaching work environment also has clinical implications for burnout syndrome. Burnout has been defined as "a psychological syndrome emerging as a prolonged response to chronic interpersonal stressors on the job" [40] (p. 103) and, therefore, as an occupational psychological syndrome [41][42][43], often affecting medical professionals, teachers, police officers, army soldiers, and many other professionals [44][45][46][47][48][49][50][51][52][53]. Certain studies have detected relationships between burnout and EI [54,55], as an important personal resource that can facilitate effective emotion regulation [56] and play a crucial role in teachers' occupational well-being models [57].…”
Section: The Role Of Emotional Intelligence and Metacognition In Rela...mentioning
confidence: 99%
“…Another study disclosed that workplace bullying is related to burnout. Furthermore, victims of bullying have an increased level of burnout and a reduced level of affective well-being (Ribeiro et al, 2021). This implies that workplace conflict could make a long-term damage.…”
Section: Links Between Workplace Conflict Work-related Stress and Emp...mentioning
confidence: 99%
“…Significantly, a 2019 survey conducted on Monster.com found that 94% of 2,081 interviewed employees had been bullied in the workplace; less dramatic data, but still very considerable, from the USA and other countries, showed that 25%–30% of the employees in the interview samples had been bullied at work in 2021 [Workplace Bullying Institute (WBI), 2021]. These effects may result in employees leaving the organization and/or going through severe psychological trauma (Ribeiro et al , 2022), which have detrimental effects on the whole organization (Kerse and Babadag, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The study presents some new aspects that contribute to advancing the existing literature on WB, fitting into the current debate in the pages of Management Research Review (Kerse and Babadag, 2019; Rai and Agarwal, 2018; Ribeiro et al , 2022). In particular, this is the first study that explicitly verifies a mediated-moderation model on DT-WB while proposing a further explanation (i.e.…”
Section: Introductionmentioning
confidence: 99%